Midnight Sun to Polar Night: A Model of Seasonal Light in the Barents Sea. (1st October 2022) - Connan‐McGinty, Stacey; Banas, Neil S.; Berge, Jørgen; Cottier, Finlo; Grant, Stephen; Johnsen, Geir; Kopec, Tomasz P.; Porter, Marie; McKee, David
Abstract: Arctic marine ecosystems are strongly influenced by the extreme seasonality of light in the region. Accurate determination of light is essential for building a comprehensive understanding of the dynamics of animal and aquatic algae populations. Current approaches to underwater light field parameterisations rely upon shortwave radiation (300–3000 nm) estimates from satellites or surface radiometry measurements to populate full radiative transfer software. Due to the inaccessibility of many regions in the Arctic, measured data is not widely available. This study presents a model of spectrally resolved underwater light in ice‐free conditions in the Barents Sea. Given a location and time, the model accounts for downwelling spectral irradiance in the photosynthetically active radiation (PAR, 400–700 nm) range ( E D PAR ) at the ocean surface from solar, lunar, and galactic light sources, modulated by local cloud cover. We demonstrate the ability to extend over the full year into the period of Polar Night, validated in both broadband PAR and spectral domains. Using a bio‐optical model of diffuse attenuation developed for the Barents Sea, we show accurate calculations to depth for inhomogeneous water columns over a spatial‐temporal range, validated against time series irradiance data from the ArcLight observatory in Ny‐Ålesund, Svalbard and in‐situ irradiance sensors deployed in the Barents Sea. Finally, in comparison to state‐of‐the‐art radiative transfer models, averaged over the water column we demonstrate a typical mean absolute error of <1 μmol m −2  s −1 in E D PAR for overcast conditions (<6 μmol m −2  s −1 for clear‐sky) and reduced execution time of factor 20. Plain Language Summary: Marine organisms in the Arctic experience large variations in underwater light levels due to prolonged periods of 24‐hr darkness and 24‐hr light. Since light is a key driver in many ecosystem dynamics, accurate modeling of Arctic marine populations can be challenging due to difficulties in determining light levels. The harsh conditions of the region can make many areas inaccessible, and often light levels fall below the sensitivity limits of widely available commercial radiometers. Additionally, most existing light field models can only predict light when the sun is above the horizon. We present a light field model that operates uninterrupted throughout the full year, able to calculate light fields from the sun above and below the horizon as well as light from the moon. The model determines spectrally resolved underwater light levels in the wavelength range that is important for biological processes. Modeled outputs have been compared and show good agreement with above surface light measurements taken in Ny‐Ålesund as well as underwater measurements recorded in the Barents Sea. Key Points: A fully seasonal model of underwater hyperspectral light in the Barents Sea, able to operate through Polar Night The model captures below horizon solar irradiance, the magnitude and timing of lunar irradiance, and is validated by in situ data The model can be used globally with the provision of an appropriate bio‐optical model for the region of interest